Analisis Kinerja Keuangan Berdasarkan Rasio Profitabilitas Pada Perusahaan Meubel CV. Yudhistira Boyolali - Febriana, Poppy Chintya, Drs. Agus Muqorrobin, MM (2017)
This study aims to determine the financial performance based on the company's profitability ratios furniture CV. Yudhistira during the years 2013 to 2015. Based on the research results are expected to improve the financial performance of the company, the company must increase the level of its profitability, especially in the NPM, ROI, and ROE is by way reduce the cost of operations and capital management efficiently.The hypothesis that the authors propose is based on the financial performance of profitability ratios seen from the Gross Profit Margin, Net Profit Margin, Return on Investment and Return On Equity. The data in this research is financial statement CV. Yudhistira form of Balance Sheet and Financial Statements for the Period of 2013, 2014, 2015. The financial ratios examined are profitability ratios using data Gross Profit Margin, Net Profit Margin, Return on Investment and Return On Equity.The results showed: (1) the financial performance of companies based on profitability ratio analysis views of Gross Profit Margin increased from year to year, it indicates good prospects of the company for the cost of sales is relatively lower than the sale. Meanwhile, if viewed from the Net Profit Margin, Return on Investment, and its return on assets fluctuate equally increased in 2014 and decreased in 2015. (2) In general, the company's financial performance for three years (2013 to 2015 ) has not been fully efficient, because the Net Profit Margin, Return on Investment and Return on Asset which fluctuates from year to year. Keywords: Gross Profit Margin, Net Profit Margin, Return on Investment and Return On Equity